Literary Studies on Heroic Journey reflection in Wrath of the Titans Movie - Fransiskus Maria Separ; Agustino A. Edwar Sia Lalu (Edumaspul: Jurnal Pendidikan, 2023)
The aim of this study is to analyze the representation of hero’s journey patterns from Perseus's journey in the film Wrath of the Titans. In this study, a qualitative descriptive method was used to describe the speech and actions of the characters. The structuralism approach is applied to analyze the building blocks of the film, namely the intrinsic elements. While the theory of heroism used to analyze the representation of heroes in the main character is the theory proposed by Joseph Campbell (2004). The results showed that Perseus as the main character is a hero, seen from the journey of his life in accordance with the pattern of the stages of the hero journey in Joseph Campbell's theory. There is a slight difference in the film, where the last pattern is refusal to return where Perseus refuses to continue his destiny as a god and prefers to return to live as a human with his son. However, this is not a vital difference that can change the heroic figure of Perseus.